Pendidikan Tata Susila pada Anak Usia Dini dalam Perspektif Islam - Handayani, Yurni (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Early Childhood Education is very important to form a generation that will be ready to replace the relay barrel of the older generation to realize a better world civilization. Early Childhood (AUD) is in its golden phase in growth and development both physically, emotionally, and spiritually. So, to get optimal and effective results, character education must be taught from an early age. Anxiety in the hearts of parents is also inseparable from children's behavior that does not reflect good behavior and ethics. This research is in the form of descriptive qualitative, library study and literature. Data analysis is carried out qualitatively through data reduction, data presentation, and conclusion drawing. The conclusion of this study is that religious and moral aspects become solui in the formation of early childhood behavior consisting of early childhood moral education towards God that moral system towards God is the initial foundation of children's creeds, then morality to the Messenger where at this stage children are taught to follow the behavior of the Apostle according to the sunnah, then morality towards parents where children learn to respect and behave well with parents, Furthermore, moral system towards the environment where we as caliphs must love and protect the environment, then moral system towards ourselves where children must love themselves by habituating good behavior towards themselves and moral system towards society where children as social beings who are able to place themselves and are able to socialize with other communities